We can save us all : a novel - Nemett, Adam (The Unnamed Press, 2018)
Welcome to The Egg, an off-campus geodesic dome where David Fuffman and his crew of alienated Princeton students train for what might be the end of days: America is in a perpetual state of war, climate disasters create a global state of emergency, and scientists believe time itself may be collapsing.